2020
DOI: 10.1007/s11664-020-08602-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trace Addition of In on Sn-Cu Solder Joint Microstructure Under Electromigration

Abstract: Recently In has been considered as an additional alloying element in Sn-rich solders primarily due to its abilities to decrease the solder melting temperature and to modify mechanical properties and microstructure. While In is an attractive candidate for addition to solder, its effect on solder microstructure is not well understood. In order to study the effect of minor In additions on Snrich solder alloys, solder joints were prepared using Sn-0.7 wt.% Cu and Sn-0.7 wt.% Cu-< 1 wt.% In alloys. Thermal aging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In their research on the relevant factors affecting electromigration polarity in Sn3.0Ag0.5Cu/Cu lead−free solder joints, Wang et al [ 31 ] found that the speed of electromigration polarity significantly increases with an increase in temperature, especially at temperatures above 100 °C. Based on this conclusion, Kelly and other researchers [ 32 ] conducted an electromigration study on Cu/Sn/Cu solder joints at temperatures above 100 °C and observed that, in the initial stage of the reaction, the Cu 6 Sn 5 grains on both sides of the interface fused. As Sn gradually depleted, the Cu matrix continued to react with Cu 6 Sn 5 to form a layered Cu 3 Sn [ 33 ].…”
Section: Introductionmentioning
confidence: 93%
“…In their research on the relevant factors affecting electromigration polarity in Sn3.0Ag0.5Cu/Cu lead−free solder joints, Wang et al [ 31 ] found that the speed of electromigration polarity significantly increases with an increase in temperature, especially at temperatures above 100 °C. Based on this conclusion, Kelly and other researchers [ 32 ] conducted an electromigration study on Cu/Sn/Cu solder joints at temperatures above 100 °C and observed that, in the initial stage of the reaction, the Cu 6 Sn 5 grains on both sides of the interface fused. As Sn gradually depleted, the Cu matrix continued to react with Cu 6 Sn 5 to form a layered Cu 3 Sn [ 33 ].…”
Section: Introductionmentioning
confidence: 93%
“…Tian et al reported that In addition had little effect on the growth of Cu 6 Sn 5 during solid-state aging of Sn-0.7Cu-xIn/Cu but strongly inhibited the growth of Cu 3 Sn [18]. In contrast, Kelly et al studied the effect of In addition on the electromigration (EM) behavior of Sn-0.7Cu solder joint and found that In addition inhibited the growth of Cu 6 Sn 5 but had no effect on Cu 3 Sn [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increasing awareness of environmental protection among the public, many countries have followed this practice and began to seek new lead-free solder to substitute the traditional harmful lead-based solder in the field of electronic packaging (Zeng and Tu, 2002;Lauro et al,2003;Seo et al, 2009;El-Ashram, 2005;Felberbaum et al, 2011;Wu et al, 2017). In recent years, the development of lead-free solder is very rapid and a variety of tin-based lead-free solder materials have appeared, such as Sn-Ag-Al (Xu et al, 2021), Sn-Bi (Xu et al, 2019), Sn-Cu (Kelly et al, 2021;Han et al,2021), Sn-3.5Ag-Cu (Shalaby et al, 2018), Sn-3.5Ag-xCu (Shalaby et al, 2017), Sn-Ag (Gumaan, 2020;Wang et al,2019), Sn-Ni (Lin, 2021;Liu et al,2019), Sn-Zn (Hu, 2021).…”
Section: Introductionmentioning
confidence: 99%